Electrochemical-reaction-induced synaptic plasticity in MoOx-based solid state electrochemical cells. Issue 6 (17th November 2016) - Yang, Chuan-Sen; Shang, Da-Shan; Chai, Yi-Sheng; Yan, Li-Qin; Shen, Bao-Gen; Sun, Young
Abstract : Solid state electrochemical cells with synaptic functions have important applications in building smart-terminal networks. Abstract : Solid state electrochemical cells with synaptic functions have important applications in building smart-terminal networks. Here, the essential synaptic functions including potentiation and depression of synaptic weight, transition from short- to long-term plasticity, spike-rate-dependent plasticity, and spike-timing-dependent plasticity behavior were successfully realized in an Ag/MoO x /fluorine-doped tin oxide (FTO) cell with continual resistance switching. The synaptic plasticity underlying these functions was controlled by tuning the excitatory post-synaptic current (EPSC) decay, which is determined by the applied voltage pulse number, width, frequency, and intervals between the pre- and post-spikes. The physical mechanism of the artificial synapse operation is attributed to the interfacial electrochemical reaction processes of the MoO x films with the adsorbed water, where protons generated by water decomposition under an electric field diffused into the MoO x films and intercalated into the lattice, leading to the short- and long-term retention of cell resistance, respectively. These results indicate the possibility of achieving advanced artificial synapses with solid state electrochemical cells and will contribute to the development of smart-terminal networking systems.